2019
DOI: 10.1103/physrevc.100.054615
|View full text |Cite
|
Sign up to set email alerts
|

Elastic transfer and parity dependence of the nucleus-nucleus optical potential

Abstract: Elastic transfer and parity dependence of the nucleus-nucleus optical potential. Physical Review C, 100(5), article no. 054615. For guidance on citations see FAQs.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 92 publications
1
9
0
Order By: Relevance
“…The results of the IP inversion were obtained with high precision and a strong Majorana term has been deduced for the total OP of the 16 O + 12 C system, which is a direct estimation of the -dependent contribution by the core exchange or α transfer. It is of interest for the present study to compare the best-fit Majorana potential (7) with the imaginary part of the inverted Majorana potential [44], and results plotted in Fig. 7 show indeed that the dynamic polarization of the OP by the core exchange or elastic α transfer can be effectively taken into account by the -dependent potential in the Gaussian form (7) suggested by Frahn and Hussein [29].…”
Section: Crc Description Of the Elastic α Transfer 12 C ( 16 O 12 C) 16 Omentioning
confidence: 74%
See 2 more Smart Citations
“…The results of the IP inversion were obtained with high precision and a strong Majorana term has been deduced for the total OP of the 16 O + 12 C system, which is a direct estimation of the -dependent contribution by the core exchange or α transfer. It is of interest for the present study to compare the best-fit Majorana potential (7) with the imaginary part of the inverted Majorana potential [44], and results plotted in Fig. 7 show indeed that the dynamic polarization of the OP by the core exchange or elastic α transfer can be effectively taken into account by the -dependent potential in the Gaussian form (7) suggested by Frahn and Hussein [29].…”
Section: Crc Description Of the Elastic α Transfer 12 C ( 16 O 12 C) 16 Omentioning
confidence: 74%
“…where W M (R) is often discussed as the Majorana potential [44], which accounts for the core-core symmetry of a light HI system like 16 O + 12 C . The best OM fit to the elastic 16 O + 12 C data at E lab = 115.9 and 132 MeV over the whole angular range Fig.…”
Section: Crc Description Of the Elastic α Transfer 12 C ( 16 O 12 C) 16 Omentioning
confidence: 99%
See 1 more Smart Citation
“…For the core-identical 16 O+ 12 C system, the elastic and inelastic α transfer channels are indistinguishable from the elastic and inelastic scattering channels, respectively. Therefore, the angular distributions of the observed elastic and inelastic 16 O+ 12 C scattering are the coherent sums of the pure scattering and α transfer amplitudes, and the total cross section is given by [2,5]…”
Section: Crc Formalismmentioning
confidence: 99%
“…The elastic transfer process was observed for several light heavy-ion (HI) systems at low energies [1], and it had been studied over the years to extract the structure information on the nucleon-and cluster spectroscopic factors (see, e.g., the review [2]) and the asymptotic normalization coefficients [3,4]. Our recent studies have shown clearly the direct link between the elastic transfer process and the parity dependence of the nucleus-nucleus optical potential (OP), a natural consequence of the core-exchange symmetry of the dinuclear system under study [5,6]. These results are an important step toward a deeper understanding of the core-exchange effect in the elastic nucleus-nucleus scattering, which has motivated a renewed interest on this topic [7].…”
Section: Introductionmentioning
confidence: 99%